Effect of Post Sizes and Citric Acid Treatment on the Bond Strength of Fiber Posts Using Self-Etch Resin Cement in Calcium Silicate–Based Sealer Treated Teeth - Klanliang, Kittipit; Dewi, Anat; Tangwattanachuleeporn, Pradtana; Louwakul, Phumisak (European Journal of General Dentistry, 2024)
Objectives This study evaluated the effects of different post sizes and citric acid (CA) treatment on the bond strength of fiber posts cemented with self-etch resin cement in teeth obturated with calcium silicate–based sealer.Materials and Methods Seventy mandibular premolars were collected and randomly distributed to either a control group (no sealer) or experimental groups obturated with calcium silicate–based sealer (iRoot SP). The experimental groups were classified by post sizes—1.25 mm (no. 1), 1.375 mm (no. 2), and 1.50 mm (no. 3)—and the irrigants used (distilled water [DW] or CA). Prefabricated fiber posts were fixed using NX3 self-etch resin cement. Push-out bond strength was tested in the coronal and middle sections of the roots.Statistical Analysis The data were analyzed using a one-way analysis of variance (ANOVA), followed by a post hoc Duncan test.Results In the coronal section, post size no. 1 with DW showed significantly lower bond strength compared to the other experimental groups (p < 0.05). In the middle section, the larger post sizes (nos. 2 and 3) with CA treatment resulted in a significant increase in bond strength compared to the control group (p < 0.05).Conclusion iRoot SP negatively affected bond strength in the middle section of the canal. However, using larger post sizes (nos. 2 and 3) with CA treatment improved bond strength in the middle section.
Keywords: bond; citric acid; fiber post; resin cement; root dentine